Dekonstruksi Otoritarianisme Hermeneutis Khaled Abou El Fadl: Relevansi Dan Implikasi Etis pada Moderasi Beragama di Indonesia - Anselmus Dore Woho Atasoge; Dominikus Doni Ola (Borneo Review, 2026)
This research aims to deconstruct Khaled Abou El Fadl's hermeneutical framework and analyze its methodological relevance in responding to the dynamics of sacred text interpretation in Indonesia. The phenomenon of interpretive authoritarianism frequently triggers socio-religious polarization, necessitating accountable epistemological instruments. Employing a qualitative method through critical textual analysis of the monumental work Speaking in God’s Name, this study dissects the pathology of "selective subjectivity" which lies at the root of absolute truth claims. The findings indicate that El Fadl offers an integrative solution through five pillars of contingency—honesty, diligence, comprehensiveness, reasonableness, and self-restraint—as ethical-intellectual verification standards in interpretation. These results confirm that the application of El Fadl's democratic hermeneutics is highly significant for the Indonesian context, particularly in strengthening the paradigm of religious moderation (wasatiyyah) and mitigating intellectual stagnation caused by the monopoly of truth by certain religious authorities.